2006
DOI: 10.1182/blood-2005-03-024463
|View full text |Cite
|
Sign up to set email alerts
|

The role of TLR2 in the inflammatory activation of mouse fibroblasts by human antiphospholipid antibodies

Abstract: Antiphospholipid antibodies (APLAs) promote inflammatory and procoagulant responses in endothelial cells and mono-cytes. Previous studies have shown that MyD88, TRAF6, and NF-B mediate cell activation by APLAs. These intermedi-ates are also used by toll-like receptors (TLRs). We investigated the role of TLRs in the cellular response to APLAs. IgGs were isolated from the plasma of 5 patients with antiphospholipid syndrome along with immunopurified anti-2-glycoprotein 1 IgG from a sixth patient. Control IgG was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 51 publications
4
56
0
Order By: Relevance
“…This observation prompted experiments with fibroblasts deficient in TLR surface expression (33,38). Our results clearly indicated that TLR-4 is required for CCL2 transcription in response to AFA-positive IgG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation prompted experiments with fibroblasts deficient in TLR surface expression (33,38). Our results clearly indicated that TLR-4 is required for CCL2 transcription in response to AFA-positive IgG.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that TLRs may also recognize host-derived ligands and contribute to autoimmune inflammatory processes (30). Furthermore, a direct recognition of TLRs by autoantibodies was recently observed in patients with antiphospholipid antibody syndrome and celiac disease (31)(32)(33)(34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ex vivo studies suggest a role for TLR2 [32][33][34], CD14 [34], GPIbα [35] and TLR8 [36] in aPLA-activated monocytes and EC. Below the role of each receptor/co receptor is described in more detail.…”
Section: Candidate Receptors For Aplamentioning
confidence: 99%
“…Several groups showed that TLR2 but not TLR4 is involved in aPL-mediated cell activation (Satta et al, 2007(Satta et al, , 2011Alard et al, 2010), and a single group report has been published on the direct binding of b2GPI to TLR2 (Alard et al, 2010). By contrast, two groups reported that siRNA-mediated inhibition of TLR2 expression on ECs or anti-TLR2 blocking antibody pretreated monocytes did not affect the aPL-induced pro-coagulation state, suggesting that TLR2 may play a limited role in the activation of unperturbed cells (Lambrianides et al, 2010;Allen et al, 2012).…”
Section: Open Questionsmentioning
confidence: 96%